EFFECTIVENESS OF DIABETIC FOOT ULCER SELF- CARE FLYER ON KNOWLEDGE AND ATTITUDE AMONG PATIENT WITH DIABETIC FOOT ULCER - Mrs. Bindhu Rajan,; Mrs. P. Rosy,; Mrs. Gayathri. T,; Mrs. Malathi Booshan,; Ms. S. Ezhilarasi,; Mrs. Aleena Meety Lal. A,; Mrs. R. Yuvashree, (The Bioscan, 2024)
Diabetes mellitus is a significant public health challenge in the 21st century, with diabetic foot ulcers (DFUs) being one of its most severe complications. DFUs are characterized by ulceration due to neuropathy and/or peripheral arterial disease in diabetic patients. This study aimed to evaluate the effectiveness of a diabetic foot ulcer self-care flyer on the knowledge and attitudes of patients with DFUs. Method: An experimental one-group pre-test post-test design was employed with 70 patients at Panimalar Medical College Hospital and Research Institute. Tools for assessing knowledge and attitudes were developed by the researcher and validated by experts. Participants completed a pre-test, followed by education via the self- care flyer. A follow-up post-test was conducted one week later. Results: The post-test scores showed a statistically significant increase in knowledge and attitudes (p < 0.05). Knowledge was significantly associated with age, sex, and educational status (p < 0.05), while attitude was linked to age and sex (p < 0.001). Conclusion: Education using the diabetic foot ulcer self-care flyer effectively enhanced knowledge and attitudes among patients, highlighting its potential as a valuable tool for increasing awareness of diabetic foot care.